Allelopatic effect of Prosopis juliflora (Sw.) DC. On seed germination growth and development of Vicia faba (Comprehensive Journal of Science, 2026)
The current study is an endeavor to recognize the  allelopathic interactions of P. juliflora. Generally, a significant inhibition of some growth parameters and pigments by all concentrations of pods and leaves extracts of P. juliflora was recognized in this study. Aqueous extracts of P. juliflora pods and leaves were prepared at concentrations of (2%, 4%, 8%, 16% and 32%) the control was distilled water. The allelopathic effect of P. juliflora pods and leaves extract as a donor species on Vicia faba as a recipient species was demonstrated with respect to its dry weight, length, leaf area and pigment fractions. Remarkably, the effect of pods extract on dry weight and both shoot and root lengths of V. faba seedlings were significantly higher than the effect of leaves extract at different concentrations. Conversely, there no significant variation in leaf area as affected with the two extracts. Regarding pigment content, the lowest values of Chl.a, Chl.b, B-carot as well as total pigments were attained at 2% concentration of pods extract.